(untitled) (The Journal of Plant Protection Sciences, 2021)
Effects of four fungi and six rhizobacteria isolates from the rhizosphere of vegetable crops was studied for suppression of root knot nematode, Meloidogyne incognita and wilt fungus, Fusarium oxysporum f. sp. lycopersici on tomato in laboratory and pot culture experiment. All the isolates were isolated by serial dilution and cultured in liquid protein supplemented broth medium and culture filtrates (CF) were prepared. In in-vitro test single eggmasses of uniform size were kept in 5ml CF in 5cm diameter Petri plates. Antifungal activity was tested by dual culture of wilt fungus with antagonist fungus and bacteria isolates in PDA media plates.